Mass Treatment of Parasitic Disease: Implications for the Development and Spread of Anthelmintic Resistance - Churcher,TS; Kaplan,RM; Ardelli,BF; Schwenkenbecher,JM; Basanez,M-G; Lammie,PJ (Karger Publishers, 2010)
There has been a dramatic increase in the use of mass drug administration to reduce the morbidity associated with helminth infections of humans, raising the likelihood that anthelmintic resistance may become a public health concern of the future. After highlighting the scope and magnitude of the chemotherapy-based helminth control programs presently in place, this chapter emphasizes the mechanisms of action of the main anthelmintic drugs in use and how resistance may develop. To date, the most established population-based mass drug administration campaigns have been against the filarial parasites which cause human on chocerciasis and lymphatic filariasis. The molecular and parasitological evidence suggesting the presence of drug resistance in human filarial parasites is reviewed and factors influencing the spread of drug resistant parasites are discussed, taking examples from veterinary helminths and the use of mathematical models. In particular, the public health impact of the development of resistance by soil-transmitted helminths, such as hookworm, is a real concern. Implications of the development of anthelmintic resistance are discussed in relation to existing control programs, emphasizing how their monitoring and evaluation is essential to prevent it becoming a major public health concern of the future.